How simple autonomous decisions evolve into robust behaviours?: A review from neurorobotics, cognitive, self-organized and artificial immune systems fields - Fernandez Leon, Jose Alberto (2014)
Researchers in diverse fields such as in neuroscience, systems biology and autonomous robotics have been intrigued by the origin and mechanisms forbiological robustness. Darwinian evolution, in general, has suggested that adaptive mechanisms, as a way of reaching robustness, could evolve by natural selection acting successively on numerous heritable variations. However, is this understanding enough for realizing how biological systems remain robust during their interactions with the surroundings? Here, we describe selected studies of bio-inspired systems that show behavioral robustness. From neurorobotics, cognitive, self-organizing and artificial immune system perspectives, our discussions focus mainly on how robust behaviors evolve or emerge in these systems, having the capacity of interacting with their surroundings. These descriptions are twofold. Initially, we introduce examples from autonomous robotics to illustrate how the process of designing robust control can be idealized in complex environments for autonomous navigation in terrain and underwater vehicles. We also include descriptions of bio-inspired self-organizing systems. ￼Then, we introduce other studies that contextualize experimental evolution with simulated organismsand physical robots to exemplify how the process of natural selection can lead to the evolution of robustnessby means of adaptive behaviors.